Peculiarities of Functional and Motor Fitness of 1St–5Th Year Students of Special Medical Department - Chernenko, Serhii; Oliynyk, Oleg; Dolynniy, Iuriy; Honcharenko, Oleg; Hordieieva, Kateryna (Physical Education Theory and Methodology, 2020)
The objective of the study was to determine the age-related peculiarities of functional and motor fitness of students of a special medical department of higher education institutions. Material and methods. The study participants were 1st year (n = 34); 2nd year (n = 14); 3rd year (n = 58); 4th year (n = 21); 5th year (n = 16) male students. One group was organized in each year of study, which added up to five experimental groups. All the students participated in physical education classes twice a week. To solve the tasks set, the following research methods were used: analysis of scientific literature, pedagogical observation, pedagogical testing, formative experiment, index method, biomedical methods, and methods of mathematical statistics. During classes, the study used the method of strictly regulated exercise (motor density of the class was 50-70%), for developing general endurance – the continuous method with covering a distance of 1,000-2,000 m (heart rate: 120-150 beats per minute), circuit and repetition methods. Results. The study results show positive changes in the functional state of the respiratory system and speed and strength abilities in the 1st-5th year students of the special medical department (p < 0.05). Conclusions. A successful development of the basic functional body systems and motor abilities in 1st-5th year students can be achieved under the influence of pedagogical conditions, namely: the method of strictly regulated exercise using exercise equipment (motor density of the class was 50-70%); the continuous method with covering a distance of 1,000-2,000 m at a slow pace (heart rate: 120-150 beats per minute); circuit and repetition methods. By the results of comparative analysis of the functional and motor fitness, the 1st-5th year male students of the special medical department show better results in tests for assessing the cardiovascular and respiratory systems, speed and strength abilities. In the 18-22 age range, according to the Ruffier index, there is an increase in the number of male students of the special medical department with a “good” and “satisfactory” cardiovascular system state and a decrease in the number of students with a “bad” result.